PEMANFAATAN MINYAK DAUN CENGKEH (SYZYGIUM AROMATCUM L.) UNTUK PENGAWETAN IKAN - Winarsyih Muhidin; Tahril Tahril (Media Eksakta, 2020)
This study aimed to examine the effect of clove leaf oil on the preservation of skipjack tuna fish. This research was conducted with variations in concentration and duration of storage. Analysis of the number of microbes was determined using the Pour method (pour plate), the organoleptic analysis used a test of the level of preference for color, aroma, texture, and taste. Analysis of protein levels used a Uv- Vis spectrophotometer and analysis of fat content used the Soxletation method.